LATEST DEVELOPMENTS AND BEST PRACTICES FOR PCO, IACOP, AND CAIA - Hugh Henry (The Journal of Intelligence, Conflict and Warfare)
On November 18, 2024, Dr. Hugh Henry presented Latest Developments and Best Practices for PCO, IACOP, and CAIA for this year’s West Coast Security Conference. The key points discussed were why an Intelligence Analyst Community of Practice (IACOP) is necessary, what the IACOP is working on to better the intelligence space, and how the IACOP operates.